2019
DOI: 10.1002/pmic.201900059
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis Identifies AIMP1 and LTA4H as FSCN1‐Binding Proteins in Laryngeal Squamous Cell Carcinoma

Abstract: Dysregulation of fascin actin‐bundling protein 1 (FSCN1) enhances cell proliferation, invasion, and motility in laryngeal squamous cell carcinoma (LSCC), while the mechanism remains unclear. Here, co‐immunoprecipitation and mass spectrometry is utilized to identify potential FSCN1‐binding proteins. Functional annotation of FSCN1‐binding proteins are performed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis. Furthermore, the protein–protein interaction network of FSNC1‐binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Loss-of-function studies showed that FSCN1 knockdown inhibited LSCC migration, invasion, and growth through the suppression of EMT 53 . Furthermore, Gao et al identified that FSCN1 binds with AIMP1 and LTA4H in LSCC, and their results suggested that AIMP1 and LTA4H were possible effectors involved in FSCN1-mediated malignant progression of LSCC 54 . In addition, expression of FSCN1 is higher in tongue squamous cell carcinoma (TSCC) tissues and cells than in adjacent non-carcinoma tissues and normal control cells.…”
Section: Biological Functions and Molecular Mechanisms Of Fscn1 In Ca...mentioning
confidence: 99%
“…Loss-of-function studies showed that FSCN1 knockdown inhibited LSCC migration, invasion, and growth through the suppression of EMT 53 . Furthermore, Gao et al identified that FSCN1 binds with AIMP1 and LTA4H in LSCC, and their results suggested that AIMP1 and LTA4H were possible effectors involved in FSCN1-mediated malignant progression of LSCC 54 . In addition, expression of FSCN1 is higher in tongue squamous cell carcinoma (TSCC) tissues and cells than in adjacent non-carcinoma tissues and normal control cells.…”
Section: Biological Functions and Molecular Mechanisms Of Fscn1 In Ca...mentioning
confidence: 99%
“…In addition to the above interaction partners, various proteins have been found to physiologically interact with FSCN1. [36][37][38][39][40][41] However, it has not been established if these interactions regulate the actinbundling activity of FSCN1.…”
Section: Regulation Of Fscn1 Activitymentioning
confidence: 99%
“…AIMP1 has been associated with poor survival in patients with head and neck squamous cell carcinoma [81] . In laryngeal squamous cell carcinoma AIMP1, in cooperation with leukotriene A4 hydrolase (LTA4H), promotes cell proliferation, migration, and invasion by binding fascin actin-bundling protein 1 [82] . As both full-length AIMP1 and its cleaved product EMAP II exhibit anti-cancer activities, strategies have been developed to improve the stability of the recombinant proteins, primarily by reducing aggregation [83] .…”
Section: Msc-associated Aarss and Aimps And Their Role In Cancer Prog...mentioning
confidence: 99%